2020
DOI: 10.1007/s10439-020-02574-1
|View full text |Cite
|
Sign up to set email alerts
|

Letter to the Editor on “Prediction of Knee Kinematics at Time of Noncontact Anterior Cruciate Ligament Injuries Based on Bone Bruises”

Abstract: The aim of the present Letter was to comment on the paper “Prediction of Knee Kinematics at Time of Noncontact Anterior Cruciate Ligament Injuries Based on Bone Bruises” from Shi et al . (Ann Biomed Eng, 2020, 10.1007/s10439-020-02523-y). Though the authors provided an extremely interesting paper on a debated topic in Sport Medicine, with a strong methodology and consistent results, caution should be used when drawing conclusions on Anterior Cruciate Ligament injury mechanism through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…The experiments were performed without biological tissue in between the sensors and the NGT. This is because it was found that the tracking performance will not be affected by the biological tissue in the study we previously carried out [ 17 ]. The magnetic field generated by live humans ranges from 20 fT to 1 nT [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments were performed without biological tissue in between the sensors and the NGT. This is because it was found that the tracking performance will not be affected by the biological tissue in the study we previously carried out [ 17 ]. The magnetic field generated by live humans ranges from 20 fT to 1 nT [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this work focuses on the application for NGT insertion, the proposed system could be applied for tracking the MIBC, endoscopic capsules, and other medical devices [ 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The more important reason is that in order to ensure that the vascular stent has sufficient radial stiffness to support the inner wall of the blood vessel, Young’s modulus and hardness of the selected stent material are higher than that of the vessel. Colombo et al elucidated the possible link between altered hemodynamics and ISR progression [ 15 ]. They found that focal re-narrowing frequently occurred after investigating from six months to 12 months.…”
Section: Introductionmentioning
confidence: 99%
“…Some natural materials that have been explored as bioactive scaffolds for cartilage engineering include chitosan, collagen, fibrin, alginate, and agarose [ 14 , 16 ]. Chitosan-based materials have been recognized as a suitable microenvironment for chondrocyte adhesion, proliferation, and differentiation when forming articular cartilage [ 17 ]. Chitosan has many attractive properties including biocompatibility, biodegradability, non-toxicity, remarkable affinity to proteins, bacterial resistance, and hemostaticity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%